Arsenic (V) removal from water using hydrotalcites as adsorbents: A critical review - Dias, Adriana Cristina; Fontes, Maurício Paulo Ferreira (Applied clay science, 2020)
Arsenic (As) is one of the most hazardous substance to human health because it is a toxic and carcinogenic chemical element. Hydrotalcites, the main class of layered double hydroxides (LDH), has emerged in the literature as promising adsorbents for remediation of waters contaminated with As. This fact is due to its high maximum adsorption capacity of As. However, determinations of residual concentration of As(V) in equilibrium solution after adsorption process, using hydrotalcites as adsorbent, are of fundamental importance and deserve special attention. In this review the term ‘hydrotalcite’ is used to describe LDH composed of Mg, Al, and CO3 (Mg-Al LDH). The World Health Organization (WHO) establishes a limit of 0.01 mg L−1 of As in drinking water. Even though hydrotalcites have high maximum adsorption capacity of As, residual concentration of As in equilibrium solution could be toxic. Therefore, adsorbents for contaminated water remediation should be chosen based not only on maximum adsorption capacity. Moreover, for As(V) adsorption researches using hydrotalcites as adsorbent, only a few studies have evaluated the chemical dissolution of structural components in hydrotalcites such as aluminum (Al) and magnesium (Mg). Currently, the presence of Al in human organisms has been correlated to potential risk of Alzheimer's disease. This subject is of extreme importance but little discussed in the literature. In this review, no comparison was made regarding the efficiency of hydrotalcites in removing As from contaminated waters, but rather an approach to its use as adsorptive material in studies on water decontamination for potability. •Critical review of As(V) removal from waters by hydrotalcite (MgAl LDH)•Equilibrium solution residual concentration of As(V) should be less than WHO limit.•Hydrotalcite has high As(V) adsorption, but structural components may solubilize.•Chemical stability analysis is crucial for As(V) adsorption using hydrotalcite.•Hydrotalcite recommendation as adsorbent for water potability requires caution.